Malignant Peripheral Nerve Sheath Tumors Show Decreased Global DNA Methylation. Issue 10 (30th August 2018) - Nix, J Stephen; Haffner, Michael C; Ahsan, Sama; Hicks, Jessica; De Marzo, Angelo M; Blakeley, Jaishri; Raabe, Eric H; Rodriguez, Fausto J
Abstract: Malignant peripheral nerve sheath tumors (MPNST) are aggressive spindle cell neoplasms that may occur sporadically, often in association with radiation exposure, or in the clinical context of Neurofibromatosis type 1. MPNST are known to harbor genetic alterations affecting the function of polycomb repressive complex 2 (PRC2), resulting in profound changes to global H3K27me3 levels. Recent evidence suggests a link between the polycomb complex and DNA methylation. Given the established epigenetic alterations found in MPNST, we aimed to further explore global methylation changes including 5-methylcystosine (5mC), 5-hydroxymethylcytosine (5hmC), and H3K27me3 levels using previously validated immunolabeling protocols in a representative cohort of 28 peripheral nerve sheath tumors (MPNST [n = 8], localized cutaneous neurofibroma [n = 10], and plexiform neurofibroma [n = 10]). MPNST showed significantly decreased levels of H3K27me3 (p < 0.0002) and 5mC (p = 0.0001) with levels of 5hmC showing borderline statistical significance (p = 0.05) when compared to localized and plexiform neurofibromas. Immunohistochemical findings of decreased H3K27me3 and 5mC further our understanding of global epigenetic alterations observable in MPNST and may provide insight into the basis of tumor progression as well as prognostic and treatment implications in the future.